Filsafat Pendidikan Pesantren di Pondok Pesantren Sabilunnaja - Abdul Muhyi Alawiy Athallah; Cepi Triatna; Sururi Sururi (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2023)
This study is aimed to analyze the educational philosophy of Islamic boarding schools at the Pondok Pesantren Sabiilunnaja, Cipeundeuy, West Bandung Regency. The approach used in this research is qualitative with descriptive method. Interviews and observations are research data collection techniques. The results of the study show that Pondok Pesantren Sabiilunnaja is based on educational philosophies in terms of ontology, epistemology, and axiology. Ontologically, the educational goals of Pondok Pesantren Sabiilunnaja are aligned with the essence of pesantren education in a comprehensive manner, including increasing cognitive, psychomotor and affective competencies. As for epistemology, education is carried out by using the traditional methods such as balagan, sorogan, muhafazoh, and muhadloroh methods which are centered on kyai and santri and tend to be bayani and irfani processes. Then axiologically, Pondok Pesantren Sabiilunnaja education has ethical and aesthetic values. The typology of educational philosophy at the Pondok Pesantren Sabiilunnaja is based on neo-modernist philosophy which has the principle of al-muhafzatu ala al-qodiimi ash-shalih wa al-akhdu bi al-jadid al-ashlah which means preserving the good things that already exist, and developing new things that are better.